Interactions langagières et corporelles lors du stage en formation initiale de masso kinésithérapie : des ajustements au sein de la triade patient/étudiant/tuteur - Delphine Guyet (Questions Vives)
This article looks at initial training in massage physiotherapy, a rehabilitation profession that aims to restore functional autonomy to the individual, and more specifically at the situation of transmitting/learning clinical reasoning in the ecological situation of a liberal internship as part of the clinical pathway. In this situation, professional gestures had been identified (Guyet, 2019). The exploration of these is pursued by focusing on the tutor-tutored co-adjustments made according to the information collected from the patient and is based on the multi-agenda analysis model of embedded concerns (Bucheton & Soulé, 2009) and that of multi-register adjustments (Saillot, 2020). We are interested in transforming the latter model to adjust it to the professional activity of masseurs-kinésithérapeutes, so as to produce resources for the initial training of this profession (Baslev, Fillietaz, Ciavaldini-Cartaut & Vinatier, 2015).